Femoral venous closure: A single-centre retrospective analysis in real world all comers with MynxGrip® vascular closure device - Harvard, Alexander; Thirunavukarasu, Shamin; Hayat, Afzal; Ullah, Abid; Aghamohammadzadeh, Reza; Holt, Cathy Mary; Malik, Nadim (Journal of Cardiology and Cardiovascular Medicine, 2020)
Background: Vascular closure devices (VCD) are routinely used to achieve haemostasis following percutaneous arterial procedures. The extravascular polyethylene-glycol based MynxGrip® device (Cardinal Health) received FDA approval for use in the closure of femoral veins, but so far limited data is available on its use, especially with concomitant use of anticoagulants. Method: This is a retrospective analysis of data from a single-centre on the effectiveness and complication rates following the use of the MynxGrip® device for femoral venous closure in patients undergoing diagnostic/interventional (temporary pacing during balloon aortic valvuloplasty, or electrophysiology) procedures utilising 5-7F sheaths. Results: 85 patients (mean age 74 years) underwent femoral venous closure with the MynxGrip® device. 51.8% were male. The rate of concomitant anticoagulant or antiplatelet use was 52.9%. Device deployment was 100% successful with full haemostasis in all cases. There were no major vascular complications (bleeding, thrombosis, or infections). There was one case of a minor small venous hematoma which did not require treatment. The mean length of stay was less than 1 day (67.1% patients discharged the same day) and overnight stay only indicated by interventional procedure. Conclusion: These data support safety and efficacy of the MynxGrip® device for femoral venous closure with same-day discharge, even with concomitant aggressive antiplatelet and anticoagulant use. It has the potential for use in other large bore venous access sites.